2017
DOI: 10.7759/cureus.1388
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Hypofractionated Radiotherapy in the Era of Concurrent Temozolomide Chemotherapy in Elderly Patients with Glioblastoma Multiforme

Abstract: IntroductionPatients with glioblastoma multiforme (GBM) over age 65 represent nearly half of those diagnosed per annum. They have a different tumor markers profile, physiologic reserve, and a median survival as low as three to four months. An optimal treatment strategy in older GBM patients remains undefined, with many patients receiving radiation in 30 treatments over six weeks, a regimen based on trials originally excluding patients over age 70. Recent studies have suggested reducing the number of treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…In Uto et al's trial, only one patient had experienced grade 4 hematological adverse event, and no grade 3 or higher nonhematological adverse event was found (12). In Greer et al's study, hypofractionated RT was well tolerated, in which no RTOG grade 3/4 toxicities was reported (17). Similarly, in our study, any grade3/4toxicity was not noted.…”
Section: Discussionsupporting
confidence: 67%
“…In Uto et al's trial, only one patient had experienced grade 4 hematological adverse event, and no grade 3 or higher nonhematological adverse event was found (12). In Greer et al's study, hypofractionated RT was well tolerated, in which no RTOG grade 3/4 toxicities was reported (17). Similarly, in our study, any grade3/4toxicity was not noted.…”
Section: Discussionsupporting
confidence: 67%
“…However, not all studies agreed on this point. Research by Joseph et al indicates the existence of a negative relationship between VEGF-related genes and the activity of the PD-L1/PD1 axis [3]. A thorough understanding of the nature of this relationship requires further work.…”
Section: Angiogenesis In Glioblastomasmentioning
confidence: 99%
“…The standard approach to glioma treatment consists in the most extensive as possible surgical resection and in adjuvant radiation strengthened by temozolomide (TMZ) administration [2]. The median overall survival (OS) oscillates between 14 and 17 months [3,4]. The survival rate of patients in a three-year follow up oscillates around 10% [5].…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive surgical resection and adjuvant radiotherapy with temozolomide (TMZ) management, tumor recurrence always occurs. In recurrent GBM, the median overall survival is estimated to be 24-44 weeks [2,3]. Increasing evidence showed that the low survival rate is closely related to GSCs [4].…”
Section: Introductionmentioning
confidence: 99%